The effectiveness of lempuyang gajah (Zingiber zerumbet) rhizome juice in reducing ectoparasite infections in mutiara catfish (Clarias gariepinus) fry - Suwartiningsih, Nurul; Afriani, Aditya Rizka (Universitas Bung Hatta, 2025)
Mutiara catfish cultivation is gaining popularity due to its fast growth, feed efficiency, and environmental resilience. However, ectoparasite infections such as Trichodina sp., Gyrodactylus sp., and Dactylogyrus sp. remain a major challenge, causing stress, inhibited growth, and potential mass mortality. The routine use of synthetic antibiotics to combat these parasites raises concerns about resistance and environmental impact, highlighting the need for safe, natural alternatives. This study evaluated the effectiveness of lempuyang gajah (Zingiber zerumbet) rhizome juice in reducing ectoparasite infections in Mutiara catfish fry. The experiment involved five treatment concentrations (0, 1, 5, 10, and 15 mL/L), each with four replications. Parameters observed included the number, prevalence, and intensity of ectoparasites. Results showed that lempuyang gajah rizome juice significantly reduced ectoparasite numbers, prevalence, and intensity, with the largest reduction observed at 15 mL/L. The decrease corresponds to increased levels of active compounds such as zerumbone, flavonoids, alkaloids, and saponins, known for their antiparasitic properties. In conclusion, lempuyang gajah rhizome juice is a promising natural and eco-friendly alternative for controlling ectoparasites in Mutiara catfish farming, offering potential solutions to issues of antibiotic resistance and food safety.